UBVRIz light curves of 51 type II supernovae - Folatelli, Gastón (2016)
We present a compilation of UBVRIz light curves of 51 type II supernovae discovered during the course of four different surveys during 1986-2003: the Cerro Tololo Supernova Survey, the Calán/Tololo Supernova Program (C&T), the Supernova Optical and Infrared Survey (SOIRS), and the Carnegie Type II Supernova Survey (CATS). The photometry is based on template-subtracted images to eliminate any potential host galaxy light contamination, and calibrated from foreground stars. This work presents these photometric data, studies the color evolution using different bands, and explores the relation between the magnitude at maximum brightness and the brightness decline parameter (s) from maximum light through the end of the recombination phase. This parameter is found to be shallower for redder bands and appears to have the best correlation in the B band. In addition, it also correlates with the plateau duration, being shorter (longer) for larger (smaller) s values.